The Effect of Power on Drying Rate of Sugarcane Bagasse Drying by Using Microwave - Melvin Emil Simanjuntak (Universitas Sultan Ageng Tirtayasa, 2020)
The sugarcane is a food plant that is widely used in daily life as a sweetener This plant is processed in a factory to produce sugar. In sugar processing, it needed a large amount of energy where its source is bagasse. As a fuel, sugarcane bagasse still has a moisture content of around 50% so the calorific value is quite low. The drying process is needed to increase this calorific value. There are many drying processes that can be used where one of them is microwave drying. The microwave drying is faster if compared to hot air. In this study, the sample of sugarcane bagasse used was chopped to a size of about 3 cm. The mass of samples used weight of 100, 125 and 150 gr and placed in an aluminum foil. The measurement of sample mass is done every minute. The electrical power used varies by 50%, 60%, 70%, 80%, 90% and 100% of the maximum power of the microwave oven. The result of the study shows a proportional reduction in moisture ratio for each power percentage difference used. The heavier sample mass will result in a smaller drying rate. The regression shows that the normal logarithmic equation is more suitable for the drying rate equation.